The Effect Of Pregnancy Exercise On Third Trimester Primigravida Anxiety In Dealing With Childbirth - Ismi Puji Astuti; Sugita Sugita; Triwik Sri Mulati (Jurnal Kebidanan dan Kesehatan Tradisional, 2021)
Background: The first labor anxiety is an unpleasant psychological condition due to physiological changes that cause psychological instability. The condition of excessive anxiety, worry, fear without cause, and stress, causes the muscles of the body to tense up, especially the muscles in the birth path to become stiff and hard, making it difficult to expand. This study analyzed the effect of pregnancy exercise on third trimester primigravida anxiety in dealing with childbirth. Methods: Quasi experimental design with nonrandomized pretest-postest control group. The sampling technique used was purposive sampling with 34 research subjects. 17 people for the treatment group were given pregnancy exercise 8 times, and 17 people for the control group were given health education about preparation for childbirth. Results: The results of data analysis using the Wilcoxon signed rank test showed that the average reduction in the treatment group was 8.00 and the control group was 3.00. The effect of pregnancy exercise on third trimester primigravida anxiety in the treatment group with a p-value (0.000) <(0.05), while the control group with a p-value (0.180)> (0.05). Conclusion: There is an effect of pregnancy exercise on third trimester primigravida anxiety in dealing with childbirth in the Wuryantoro Health Center work area.